Method development, validation, and impurity measurement of β-estradiol from radiolabeled [131I]β-estradiol using radio-high-performance liquid chromatography for radioligand of saturation binding assay - Isti Daruwati; Abednego Kristande Gwiharto; Hendris Wongso; Tri Hanggono Achmad; Mukh Syaifudin; Muchtaridi Muchtaridi (Wolters Kluwer Medknow Publications, 2023)
β-estradiol is an estrogen steroid hormone and acts as an estrogen receptor agonist. Radiolabeled β-estradiol is widely used as a radioligand for binding assays. In this present study, the synthesis of [131I]β-estradiol has been successfully carried out. Accordingly, the measurement of the radiochemical purity (RCP) value and the presence of chemical impurities are needed. To validate the method for identifying the RCP and chemical impurities from [131I]β-estradiol using high-performance liquid chromatography (HPLC). The synthesis of [131I]β-estradiol was accomplished by a radioiodination reaction, and the RCP was determined by radio-HPLC. The method for β-estradiol measurement was validated by reversed-phase HPLC radio-analytical employing ultraviolet-visible (UV-Vis) and radioactive detector. The method for radio-HPLC analysis was validated and established using a C-18 column and MeCN: H2O (55:45 v/v) as the mobile phase. The following conditions were applied: a flow rate of 1.2 mL/min, isocratic, and a UV-Vis detector at 280 nm. The RCP of [131I]β-estradiol measured by thin-layer chromatography and radio-HPLC was 99.27% ± 1.25% and 95.75% ± 2.41%, respectively. The validation parameters were appropriate and met the requirements for acceptance. HPLC analysis was able to identify the presence of unlabeled estradiol (24.51%-27.29%) in the mixture of [131I]β-estradiol. As a result, purification using preparative HPLC or other methods will be required in future studies.